Conversión Alimenticia en Cuyes colorados y pintados en la Etapa de Crecimiento en la Cuarta Progenie de un Cruce Genético de Tipo Absorbente - Landeta Martínez, Norma Yeseña (2018)
The Cavia porcellus production represents a significant issue in the agriculture and livestock economy of Ecuador, taking into account that in recent years there have been exports of cuyes to other countries. In all cattle exploitation, food is one of the factors that has the most significant impact on animal productivity. Therefore, the primary objective of this project was to determine the feed conversion in red-colored AND mottled red-colored and white CUYES in the growth stage with the fourth line of genetic crossbreeding of the absorbent type made in CEASA, the researcher proceeded to verify the selection characteristics of the third progeny, appreciating between the two progenies from the weights found in the records, then comparative analyzes were applied to evaluate the absorbent cross. Four categories were identified in the stage of growth of red-colored and mottled red-colored and white cuyes; these were defined by two aspects, color and sex, after that ADEVA and DUNCAN statistical analyzes were applied, so the results of the categories of red-colored cuyes in growth were associated with a minimum weight average of 646.2 g and maximum of 803.5; while in mottled red-colored and white cuyes a minimum of 287.6 g and maximum of 681.1 g was obtained during 13 weeks. Therefore, the research must talk about the consumption of food in this time a minimum average of 2502.52 g and maximum of 3182.38 in red-colored and mottled red-colored and white cuyes (females and males) in the growth stage. Finally, the general food conversion in red-colored cuyes has values such as a maximum of 5.28% and a minimum of 3.69%; however, in mottled red-colored and white cuyes, maximum values of 8.83% and a minimum of 4.00% are obtained. It is concluded that the animals with the best feed conversion in this stage are red-colored cuyes, establishing a minimum value of 3.69% that is the fair conversion values range in this species